Yield and ultimate strengths determination of a blind bolted endplate connection to square hollow section column. (15th March 2016) - Wang, Zhi-Yu; Wang, Qing-Yuan
Highlights: Tensile behaviour of a blind bolted endplate connection is experimentally evaluated. Distinct failure modes and geometric parameters are outlined and discussed. Finite element models allowing for connection features agree with test results. Analytical models are proposed for strength prediction with good accuracy. Abstract: This paper evaluates the yield and ultimate strengths of a blind bolted endplate to square tubular column connection in joint tensile region. It outlines a research work of eleven connection tests with focus on the strengths of the connection components under tensile loads. The influences of the bolt gauge width, slenderness of tubular columns and bolt size details on the strengths of the connections in three failure modes are reported. Based on the experimental test results, yield strength determination methods are examined and discussed on the basis of deformations of the tube connecting face and the overall connection. Finite element models explicitly allowing for the configuration details of the Hollo-Bolt are then presented and compared with the test results. Subsequently, an analytical model is proposed for the prediction of yield strength with due consideration given to the plastification of SHS column and combined action of the blind bolt related to three failure modes. Based on an augmented consideration of membrane effect and circumferential locking action of the Hollo-Bolt, the analytical model is also extended for the prediction of ultimate strength. Additionally, two geometric parameters in characterizing the failure modes of the connection are discussed from a numerical parametric study. The analytical results presented in this paper provide some essential information for the strength design recommendations of such a blind bolted endplate connection to square tubular column.